2014
DOI: 10.3758/s13415-014-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Genes of the dopaminergic system selectively modulate top-down but not bottom-up attention

Abstract: Cognitive performance is modulated by the neurotransmitter dopamine (DA). Recently, it has been proposed that DA has a strong impact on top-down but not on bottom-up selective visual attention. We tested this assumption by analyzing the influence of two gene variants of the dopaminergic system. Both the catechol O-methyltransferase (COMT) protein and the dopamine transporter (DAT) protein are crucial for the degradation and inactivation of DA. These metabolizing proteins modulate the availability of DA, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 79 publications
1
17
1
Order By: Relevance
“…Additionally, most previous studies selected only one response inhibition task, thereby failing to allow the assessment of the specificity of any observed associations within the domain of inhibitory function. Finally, the only response inhibition studies combining the two polymorphisms (Colzato, van den Wildenberg, Van der Does, & Hommel, 2010;Congdon et al, 2009;Gurvich & Rossell, 2014;Schneider et al, 2014;Stokes et al, 2011) did not investigate or report statistical interactions of the two polymorphisms with regards to inhibition performance, leaving open whether such geneegene interaction effects may exist.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, most previous studies selected only one response inhibition task, thereby failing to allow the assessment of the specificity of any observed associations within the domain of inhibitory function. Finally, the only response inhibition studies combining the two polymorphisms (Colzato, van den Wildenberg, Van der Does, & Hommel, 2010;Congdon et al, 2009;Gurvich & Rossell, 2014;Schneider et al, 2014;Stokes et al, 2011) did not investigate or report statistical interactions of the two polymorphisms with regards to inhibition performance, leaving open whether such geneegene interaction effects may exist.…”
Section: Introductionmentioning
confidence: 95%
“…However, opposing evidence has also been obtained (Kim, Kim, & Cho, 2006). In a recent study, 9R homozygotes performed worse on the incongruent condition of a Stroop task compared to 10R homozygotes and 9/10 heterozygotes (Schneider, Schote, Meyer, & Frings, 2014). A genetic imaging study of adolescents showed that during response inhibition, the homozygosity for the 10R allele may be associated with increased activation in frontal, medial, and parietal regions compared to non-10R carriers (Braet et al, 2011), although the opposite pattern was observed in adult ADHD patients (Dresler et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The latter result fits with the missing influence of nicotine on NP as nicotine leads to a heightened acetylcholine transmission. However, studies that analyze the influence of dopamine on selective attention in humans are scarce (see Schneider, Schote, Meyer, & Frings, 2015, for an exception) but might prove quite useful to disentangle the different cognitive processes contributing to NP effects.…”
Section: Conclusion For and Future Directions In Negative Primingmentioning
confidence: 99%
“…This sample is part of a larger sample that has also been analyzed in regard to several polymorphisms (see[45,46])3 Recently,[47] have reported on the low extent of genetic heterogeneity in German samples. In their study, only a slight north-south gradient was detectible, though this difference was still several times smaller than those between samples drawn in Germany and samples in other Germanic populations, accounting for far less than 5 % of the total variance.…”
mentioning
confidence: 99%